(3GdRHOI aj TQM bUjOI GdHQOIs - (3GdLQLGhj GdCRgQj GdeUQj, Rjf GdOjf, GdhbGO, NGdO Hf YHO Gddg Hf CHj HcQ, J (B905 (3g`s ((3eMeO SYjO Hf MeRI GdefbGQs)
(3ChdgG (B:s
(3CeG HYO MeOG ddg eSJMb GdJMejOajbhd NGdO Hf YHO Gddg GdCRgQj bO SCdJfj CjgG GdCN Cf CVY TQMG Ydi HQOI GdeOjM ddTjN GdHhUjQjCJe JhVjMs
(3BNQgG (B:s
(3aEfc CeQJfG HGdUdGI hGdSdGe Ydjg bOjeG abdJ Ef Gddg hdeGFcJg jUdhf Ydi GdfHj jG CjgG GdPjf BefhG UdhG Ydjg hSdehG JSdjeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 297s
(3eYLe GdeDdajf(B: 1 / 668s
(3cTa GdXfhf(B: 2 / 1332s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs